IL28B Polymorphism Does Not Determine Outcomes of Hepatitis B Virus or HIV Infection - Martin, Maureen P. (The University of Chicago Press, 2010)
An IL28B haplotype strongly determines the outcome of natural and interferon-α treated hepatitis C virus (HCV) infection. To assess whether the polymorphism marking the haplotype (rs12979860) also affects other interferon-α responsive chronic viral illnesses, namely hepatitis B virus (HBV) and human immunodeficiency virus (HIV) type 1 infections, we genotyped 226 individuals with HBV persistence, 384 with HBV recovery, and 2548 with or at high risk for HIV infection. The C/C genotype of rs12979860 was not associated with HBV recovery (odds ratio, 0.99), resistance to HIV infection (odds ratio, 0.97), or HIV disease progression (P>.05). This IL28B single-nucleotide polymorphism affects the immune response to HCV but not to HBV or HIV.